Impact of bleeding and thrombosis on outcome of 945 COVID-19 VV-ECMO cases from a German registry - Herrmann, Johannes; Schade, Janno; Meybohm, Patrick; Paschke, Noah; Hübsch, Martha E.; Notz, Quirin; Groene, Julie; Röder, Daniel; Kranke, Peter; Merten, Michaela L.; Landoll, Micha; Spieth, Peter; et al. (Frontiers in Medicine, 2025)
Bleeding and thromboembolic events (BTE) increase the mortality of COVID-19 acute respiratory distress syndrome (ARDS) treated with extracorporeal membrane oxygenation (ECMO). The current analysis aimed to assess frequency and determinants of BTE according to their location and severity in a retrospective analysis of the German ECMO COVID-19 registry. Logistic regression was applied to identify factors influencing ICU survival as well as variables associated with risks of BTE. In total, 708 of 945 patients (75%) suffered from BTE. Overall, 1,348 events were registered, including 406 (30%) major bleeding and 258 (19%) major thromboembolic events. Most common major bleeding locations were intracranial (n = 133, 10%) and pulmonary bleeding (n = 116, 9%). In-ICU survival was 35, 46% without BTE and 22% with major bleeding (p < 0.05). In summary, major bleeding was a core outcome-determinant of COVID-19 ECMO mortality with intracranial major bleeding as the most devastating complication (OR: 5.3; CI: 2.9–9.9; p < 0.001). Neither major thromboembolism nor minor BTE impacted ICU-mortality. Potentially modifiable factors associated with major bleeding included prolonged duration of ECMO >14 days (OR: 2.9; CI 1.8–4.7; p < 0.001) and platelet counts <100.000/μL ≥ 72 h (OR: 2.0; CI 1.1–3.6; p = 0.018). Hence, prevention, early recognition and treatment of major bleedings are key to increase the survival of COVID-19 ECMO. In this regard, our data indicate that the implementation of early weaning strategies to minimize duration of ECMO therapy and prevention of prolonged thrombocytopenia with platelet counts <100.000/μl ≥ 72 h could decrease the risk of devastating bleeds and could ameliorate survival.Clinical trial registrationRegistered in the German Clinical Trials Register (study ID: DRKS00022964), retrospectively registered, September 7th 2020, https://drks.de/DRKS00022964.